SOSIALISASI PENGOLAHAN SAMPAH TINGKAT RUMAH TANGGA PADA IBU PKK KELURAHAN ULAK KARANG UTARA - Rini Asmariati; Era Triana; Dwifitra Y; Jumas Jumas; Nori Yusri; Vivi Ariani; Wenny Widya Wahyudi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
In Kelurahan Ulak Karang Utara, Padang City, it produces garbage that comes from households every day. This waste is always thrown into the trash cans and then transported by the Kelurahan cleaners, thrown into the TPS, and finally dumped into the TPA. However, currently, the community has not yet implemented waste processing. Also, PKK mothers do not understand the benefits that can be obtained from sorting the waste in the household. The purpose of this activity is to increase knowledge and understanding as well as public awareness about waste processing to increase family income. This activity was carried out in Ulak Karang Utara Village, Padang City, with the target of PKK women's activities in Ulak Karang Village. The activity method used was counseling and training. The implementation of the activity began with an initial meeting between the presentation team, the village head, and the PKK's head, Ulak Karang Utara village. Furthermore, socialization was carried out on household-level waste processing at routine PKK women's meetings. At the end of the socialization, a question and answer session was conducted to see the participants' level of knowledge and understanding. The socialization of waste processing at the household level is the first step for PKK women of Ulak Karang Utara Village to sort waste from the beginning and ultimately reduce the amount of waste generated in the TPA. Waste sorting and processing training can be processed into compost so that it can increase family income. It is hoped that from this activity, PKK women can change their minds that sorting waste is carried out from the start starting at home.